Scheduled Caste Population in an Indian Hill State A Case of Himachal Pradesh - Kant, Surya (National Geographical Journal of India, 2022)
Late Professor S.L.Kayastha, a highly sophisticated, methodological, and humane persona, left an imprint on the discipline of geography in general and Indian geography in particular. For his remarkable contribution, he was elected President of several academic and professional bodies including the National Association of Geographer of India (NAGI). He was innovative and reflective. He was among the pioneers who could realize the importance of introducing teaching and research in sub-field of our discipline such as Population Geography and Environmental Geography including disaster management. He was a teacher par excellence. He made his janambhumi (place of birth), karambhumi (work area) too. He was born in Dev Bhumi (Himachal Pradesh) and selected the state for his doctoral research degree on the theme: Himalayan Beas Basin: A Study in Habitat, Economy and Society. When, I was invited by Professors V.K.Kumra and R.S.Yadava to contribute a paper for the special number of National Geographical Journal of India to be brought out as a tribute in the memory of Professor S.L.Kayastha, I decided to contribute a paper on any theme focusing on Himachal Pradesh. This paper is my humble tribute to the memory of my beloved teacher.